Preoperative evaluation of red blood cell distribution width as a promising biomarker for discriminating between benign and malignant breast tumors and assessing breast cancer activity - Ajay Singh Thakur; Chandrashekhar Indoria; Ruby Sahu; Pratima Kujur; Renuka Gahine (Indian Journal of Pathology and Microbiology)
Background: The red cell distribution width (RDW) has been recognized as a new prognostic factor in various pathophysiological states including breast cancers. The aim of this study was to compare the RDW values between patients diagnosed with benign and malignant breast tumors and to evaluate the potential of elevated RDW as a biomarker for breast cancer activity. Materials and Methods: A cross-sectional study compared RDW values in age-matched cohorts diagnosed with benign and malignant breast lesions and correlated them with prognostic factors for malignant breast tumors. The study excluded individuals with inflammatory disorders, pre-neoplastic disease, hematological disorders, or those taking immunosuppressive or anti-inflammatory medications. The RDW values were measured using an automated hematology analyzer. The study’s statistical analysis was conducted using SPSS software at a significance level of 0.05. Results: RDW demonstrated a statistically significant elevation in the cohort of patients with malignant breast tumors, those with metastatic breast tumors, a greater number of infiltrated axillary lymph nodes, larger tumor diameter, and a higher grade of the primary tumor mass. Conclusions: The findings of this study suggest that RDW has the potential to serve as a biomarker for assessing breast cancer activity and could offer substantial advantages in clinical contexts. The present study is not without limitations, and the authors suggest that a larger multicenter prospective study be conducted to further validate it’s efficacy over an extended duration.